The Relation between Foreign Direct Investment Inflows and Tourism Development in Nepal - Bhandari, Lokraj (Unity Journal, 2022)
Natural beauty and cultural institutions are perennial factors for tourism development with a competitive advantage in Nepal. However, the country has not been able to capitalize on those natural and cultural resources for the benefit of the people at a large scale. Without in-depth research on the prospect of the tourism industry and its application, Nepal has been lagging behind many of the countries of the world even in the twenty-first century. Nevertheless, existing scholarship on the relation between ‘FDI (Foreign Direct Investment) inflows’ and ‘tourism development’, has remained incomplete. Therefore, this study has set the specific objectives of finding and analyzing the causal relationship between these two variables using the time series data of Nepal from 1995 to 2019. It has followed the causal-comparative research design to meet the objectives asserting the dependent variable: ‘net FDI inflow’ and independent variable: ‘tourism development’, first. Then, the discourse has forwarded interchanging the dependent into independent and independent into dependent one. This analysis finds a bi-directional relationship between FDI inflow and tourism development in the short run. The arrival of one international tourist causes a 68 USD increase in ‘net FDI inflows’ and an increase in one USD from him increases a 0.17 USD in FDI. Similarly, a one USD increase in net FDI inflows causes a 0.76 USD increase in income from international tourism. However, it has asserted no long-run relationship between these variables. Importantly, these findings help the government and policymakers formulate and implement the right policies and programs for the sustainable tourism development of Nepal.